Prognostic evaluation of segmental ureterectomy combined with chemotherapy in high-grade non-metastatic ureteral cancer: a study based on the SEER database - Yu Xia; Bin-Bin Ma; Meng-Yun Li; Xi Liu; Dan-Feng Xu; Tao Huang (Scientific Reports, 2024)
Abstract This study evaluates the survival outcomes of segmental ureterectomy (SU) combined with chemotherapy in patients with high-grade non-metastatic ureteral cancer (UC) using data from the SEER database. A total of 1757 patients with Grade III-IV non-metastatic UC were analyzed. Overall survival (OS) was assessed through Kaplan–Meier analysis, and independent prognostic factors were identified via Cox regression. A Nomogram model was developed and evaluated using the concordance index, area under the time-dependent ROC curve, calibration curves, and decision curve analysis. The 1-, 3-, and 5-year OS rates were 82.8%, 55.6%, and 42.8%, respectively. Age, treatment protocol, T stage, and N stage were significant prognostic factors. Both SU + chemotherapy and radical nephroureterectomy (RNU) + chemotherapy demonstrated comparable survival outcomes, outperforming surgery alone, particularly in patients aged 70 and older. The Nomogram demonstrated high predictive accuracy and clinical utility. These findings suggest that SU + chemotherapy offers survival benefits similar to RNU + chemotherapy, making it a viable option, especially for elderly patients or those with impaired renal function.